2009
DOI: 10.1111/j.1469-8137.2009.03010.x
|View full text |Cite
|
Sign up to set email alerts
|

Rhizosphere bacterial communities associated with disease suppressiveness stages of take‐all decline in wheat monoculture

Abstract: International audience• The decline of take-all disease (Gaeumannomyces graminis var. tritici), which may take place during wheat monocropping, involves plant-protecting, rootcolonizing microorganisms. So far, however, most work has focused on antagonistic fluorescent pseudomonads. Our objective was to assess the changes in rhizobacterial community composition during take-all decline of field-grown wheat. • The study was based on the development and utilization of a taxonomic 16S rRNA-based microarray of 575 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
92
4
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(104 citation statements)
references
References 72 publications
4
92
4
1
Order By: Relevance
“…3), but also at phylum (Table 6) and genus levels (Tables S1 & S2). Sanguin et al (2009) showed that Verrucomicrobia was one of the prevalent phyla during the outbreak of wheat take-all disease, which was different from the finding in the present study that the abundance of this phylum was higher in healthy (5.06 % in rhizosphere soil and 0.40 % in roots) than diseased plants (2.85 % in rhizosphere soil and 0.32 % in roots). This may be explained by the low relative abundance of Verrucomicrobia accounted for the total sequences, 3.96 % in rhizosphere soil and 0.36 % in roots on average, variation in the initiator of different soil-borne diseases (Van Elsas et al 2002) and difference in land management (Rescia et al 1994).…”
Section: Discussioncontrasting
confidence: 99%
“…3), but also at phylum (Table 6) and genus levels (Tables S1 & S2). Sanguin et al (2009) showed that Verrucomicrobia was one of the prevalent phyla during the outbreak of wheat take-all disease, which was different from the finding in the present study that the abundance of this phylum was higher in healthy (5.06 % in rhizosphere soil and 0.40 % in roots) than diseased plants (2.85 % in rhizosphere soil and 0.32 % in roots). This may be explained by the low relative abundance of Verrucomicrobia accounted for the total sequences, 3.96 % in rhizosphere soil and 0.36 % in roots on average, variation in the initiator of different soil-borne diseases (Van Elsas et al 2002) and difference in land management (Rescia et al 1994).…”
Section: Discussioncontrasting
confidence: 99%
“…As others have found in community-based analyses of suppressive soils (Sanguin et al, 2009;Mendes et al, 2011;Rosenzweig et al, 2012), no single phylum was uniquely associated with disease suppression in the strawberry wilt microbiome (Table 1 and Supplementary Tables S4, S5 and S6). Instead, our identification of antibiotic-producing Streptomyces as participating in the suppression of Fusarium wilt also required culture-based approaches that have long implicated specific microorganisms in those instances where the etiology of specific soil suppressiveness has been at least partially resolved.…”
Section: Discussionmentioning
confidence: 92%
“…have long been known to contribute to the suppression of common scab of potato caused by pathogenic Streptomyces spp. (Bowers et al, 1996;Lorang et al, 1989), community-based studies of such soils have shown that multiple taxa are associated with suppression but have not resolved functionally active agents at the species or subspecies level in either pathosystem (Sanguin et al, 2009;Rosenzweig et al, 2012). A third study, guided by a community-based approach and on which our work was modeled, also identified multiple phyla in a soil suppressive of damping-off disease caused by Rhizoctonia solani, but culturebased methods were needed to identify specific strains of an antibiotic-producing Pseudomonas inhibitory to the pathogen (Mendes et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, if we consider bacterial-fungal biofilms, it is clear that fungi can promote distinct differences in bacterial development by contributing to a distinctive ecological niche, within which bacteria exhibit physiological differences, such as resistance to antibiotics, stress, and an altered expression of virulence genes, compared to free-living bacteria (153,154,306). There is also body of literature that points to the influence of fungi on bacterial community structure at both the taxonomic and functional levels, notably in the mycorrhizosphere and pathorhizosphere (119,332,370) but also in other contexts, such as cheese and wine production (2,58,173,261,386). However, it is a significant challenge to make the link between cell-cell communication in BFIs and community-level organization.…”
Section: Consequences Of Bacterial-fungal Interactions For Participatmentioning
confidence: 99%